Influencing hardness and wear during the dynamic tempered microinjection molding process by considering isothermal holding time. Issue 2 (28th July 2016) - Fischer, Christopher; Seefried, Andreas; Merle, Benoit; Göken, Mathias; Drummer, Dietmar
Abstract : For semicrystalline thermoplastic parts it is well known that increasing isothermal holding temperature can affect inner component properties, respectively, crystalline structure (e.g., morphology, degree of crystallization, crystal modification, etc.) and, therefore, resulting global component properties such as hardness and wear. Nevertheless, in literature there is no explicit focus on the effect of isothermal holding time during dynamically tempered injection molding process. In this article, semicrystalline microcomponents have been injection molded by varying isothermal holding time within the material's crystallization temperature area. As materials, POM‐C, as a material with relatively high crystallization kinetic, and PA 12, as a material with medium crystallization kinetic, were used. To evaluate the effects on hardness and wear, nanoindentation measurements as well as pin‐on‐disc wear tests were performed. Results show that for fast crystallizing POM‐C an isothermal holding step has no significant influence on inner component and resulting global component properties. For slower crystallizing PA 12, however, the morphology and the degree of crystallization could be influenced and, as a result, hardness could be increased by 21% while wear could be reduced by 30%. POLYM. ENG. SCI., 57:121–128, 2017. © 2016 Society of Plastics Engineers